2019
DOI: 10.1101/747782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental gene expression differences between humans and mammalian models

Abstract: 14Identifying the molecular programs underlying human organ development and how they differ from 15 those in model species will advance our understanding of human health and disease. 16 Developmental gene expression profiles provide a window into the genes underlying organ 17 development as well as a direct means to compare them across species. We use a transcriptomic 18 resource for mammalian organ development to characterize the temporal profiles of human genes 19 associated with distinct disease class… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
4
16
0
1
Order By: Relevance
“…To assess whether the organ development trajectories for these genes differ substantially between mouse and human, we investigated the similarity of spatiotemporal gene expression profiles for the two species. We found that 78 and 82% of the entire set of genes under study showed the same trajectory for cerebellum and brain respectively, with no significant differences observed between WoL, and in concordance with what was observed for the entire set of genes with data available 25 ( Sup Fig 2 ). Similarities in gene expression will not always imply conserved phenotypes between mouse and human, but they can serve as a proxy for how translatable to human disease the findings for these genes are.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…To assess whether the organ development trajectories for these genes differ substantially between mouse and human, we investigated the similarity of spatiotemporal gene expression profiles for the two species. We found that 78 and 82% of the entire set of genes under study showed the same trajectory for cerebellum and brain respectively, with no significant differences observed between WoL, and in concordance with what was observed for the entire set of genes with data available 25 ( Sup Fig 2 ). Similarities in gene expression will not always imply conserved phenotypes between mouse and human, but they can serve as a proxy for how translatable to human disease the findings for these genes are.…”
Section: Resultssupporting
confidence: 87%
“…Human gene expression (RPKM) across development for brain, cerebellum, heart, kidney, liver, ovary and testis was obtained from Cardoso-Moreira et al 23 https://apps.kaessmannlab.org/evodevoapp/ [Downloaded 10.08 .21] Data on comparison of temporal trajectories between human genes and their orthologs in mouse for brain and cerebellum was obtained from Cardoso-Moreira et al 25 .…”
Section: Gene Expression Across Developmentmentioning
confidence: 99%
“…9d). In line with studies linking phenotypic severity to expression pleiotropy 19,41 , we found that the dynamic genes shared between the two neuron types are under stronger constraint than genes dynamic in one cell type only (Fig. 3e, Extended Data Fig.…”
Section: Cell Type-defining Transcriptional Programssupporting
confidence: 87%
“…We used different metrics of gene essentiality: (i) LOEUF score (loss-of-function observed/expected upper bound fraction) 39 from the Genome Aggregation Database (gnomAD), which ranks genes along a continuous spectrum of tolerance to loss-of-function variation based on human exome and genome sequencing data (in vivo); (ii) a measure of in vivo essentiality that combines various essentiality scores (RVIS, pLI, Phi, missense Z-score, LoFtool and s het ) to rank genes based on human exome and genome sequencing data 38 ; (iii) a measure of in vitro essentiality that combines viability scores from CRISPR-Cas9 screens on human cell lines 38 . We obtained the human inherited disease gene list from the manually curated Human Gene Mutation Database (HGMD, PRO 17.1) 42 , and only used genes with disease-causing mutations as described previously 41 . We used the genes that based on the mapping to the Unified Medical Language System (UMLS) were linked to the high level disease types 'Nervous system' or 'Psychiatric', and split these genes into two groups based on whether a gene was also linked to the high level disease type 'Developmental' (developmental n=373; other n=200).…”
Section: Essential and Disease-associated Genesmentioning
confidence: 99%
“…Proteins known to be expressed in humans were also found to be enriched in frogs, but surprisingly not in mice or pigs [35]. It is unsurprising then that frogs may find their way into more translatable research in the future [36], especially given that half of human genes differ from their mouse orthologs in different developmental trajectories, including more than 200 disease genes associated with brain, heart, and liver diseases [37]. These differences can impact the proteomes, and therefore phenotypes, between humans and mice.…”
Section: Proteomes Of Larger Speciesmentioning
confidence: 99%